2002
DOI: 10.1212/wnl.59.6.904
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and cognitive function

Abstract: Abstract-Objective:To investigate the association between migraine and cognitive ability among members of a longitudinal birth cohort study. Methods: Headache status was determined at age 26 (migraine, tension-type headache [TTH], headache-free control subjects) according to International Headache Society criteria, and data relating to cognitive and academic performance from ages 3 to 26 years were analyzed. Results: Study members diagnosed with migraine were subtly but significantly impaired, compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 34 publications
10
105
3
Order By: Relevance
“…17,26 However, none of our subjects had depression according to clinical evaluation at the time of the neuropsychological investigation. Although there is some evidence of cognitive impairment in persons with life-long migraine, 27,28 in our patients, history of migraine or mood change did not significantly associate with cognitive performance. There was also an overrepresentation of men among our subjects (approximately two thirds), which deviates from that generally seen in CADASIL.…”
Section: Discussioncontrasting
confidence: 78%
“…17,26 However, none of our subjects had depression according to clinical evaluation at the time of the neuropsychological investigation. Although there is some evidence of cognitive impairment in persons with life-long migraine, 27,28 in our patients, history of migraine or mood change did not significantly associate with cognitive performance. There was also an overrepresentation of men among our subjects (approximately two thirds), which deviates from that generally seen in CADASIL.…”
Section: Discussioncontrasting
confidence: 78%
“…However, the inverse relationship between migraine and socioeconomic status has not been confirmed in studies outside the United States (Launer, Terwindt, Ferrari, 1999;O'Brien, Goeree, Streiner, 1994;Rasmussen, 1992;Waldie et al, 2002), in these studies no difference in migraine prevalence by socioeconomic status was found. Nevertheless, the links between social class and health outcomes have well been demonstrated in the literature (Wilkinson & Marmot, 2003;Wilkinson & Pickett, 2006).…”
Section: Introductionmentioning
confidence: 77%
“…In an important, longitudinal study, Waldie et al 18 found impaired verbal skills in a migraine group when compared to a control group, more evident between 3-to-13-year-old migrainer children.…”
Section: Discussionmentioning
confidence: 99%